2022
DOI: 10.5334/tohm.690
|View full text |Cite
|
Sign up to set email alerts
|

The Conundrum of Dystonia in Essential Tremor Patients: How does One Classify these Cases?

Abstract: Background:The relationship between essential tremor (ET) and dystonia has been long debated and the boundaries between these disorders remain unclear. Here, we highlight the diagnostic uncertainty that can arise when observing dystonic postures in patients who have received ET diagnoses.Methods: An international panel of seven movement disorders neurologists from five countries reviewed the clinical history and videotaped neurological examinations of five individuals diagnosed with ET who also had various fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Furthermore, we have here shown that patients with ET + DS have some similarities with both ET and TwD and therefore we cannot conclusively claim whether the presence of soft dystonic signs is prodromal to the development of overt dystonia 15,16 or instead represent an unspecific finding that is unrelated to the tremor syndrome. [21][22][23] Importantly, both AAO and disease duration were similar between the groups and therefore these features cannot explain the differences we found between the groups. FH was found to be lower in TwD than in ET/ET + DS.…”
Section: Discussionmentioning
confidence: 67%
“…Furthermore, we have here shown that patients with ET + DS have some similarities with both ET and TwD and therefore we cannot conclusively claim whether the presence of soft dystonic signs is prodromal to the development of overt dystonia 15,16 or instead represent an unspecific finding that is unrelated to the tremor syndrome. [21][22][23] Importantly, both AAO and disease duration were similar between the groups and therefore these features cannot explain the differences we found between the groups. FH was found to be lower in TwD than in ET/ET + DS.…”
Section: Discussionmentioning
confidence: 67%
“…The phenomenology of these maneuvers is variable, but consistent in each individual patient. A common phenomenon consists of placement of a finger on the chin or hand in the occipital area of the head 12 ; others include touching the lower face or the posterior neck, and, less commonly, the upper face 24 . Another maneuver involves raising the arms without touching the head 29 .…”
Section: Resultsmentioning
confidence: 99%
“…Currently, there is no test to definitively diagnose iCD, and the gold standard is a clinical diagnosis based on history, clinical features, and phenomenology. Studies on iCD have often relied on clinicians’ experience to identify diagnostic features, but differences of opinion have emerged, even among experts, particularly if features are subtle or less severe 11‐13 . The International Parkinson and Movement Disorder Society's Dystonia Study Group convened a consensus panel to characterize the clinical features of iCD, review terminology, and suggest internationally agreed diagnostic criteria.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Developing objective biomarkers for soft signs like dystonia and ataxia is one approach toward more accurate classification. 6 Electrophysiological tremor analysis may offer another approach, as relatively distinct electrophysiological signatures are known to exist in various tremor syndromes. For instance, the frequency and positional features of tremor on combined surface electromyography (EMG)-accelerometric tremor analysis are characteristically different in parkinsonian tremor, ET, and cerebellar tremor.…”
mentioning
confidence: 99%
“…Developing objective biomarkers for soft signs like dystonia and ataxia is one approach toward more accurate classification 6 . Electrophysiological tremor analysis may offer another approach, as relatively distinct electrophysiological signatures are known to exist in various tremor syndromes.…”
mentioning
confidence: 99%